Controlling the Urban Fabric: The Complex Game of Distance and Proximity in European Upper‐Middle‐Class Residential Strategies. (16th October 2012) - Andreotti, Alberta; Le Galès, Patrick; Fuentes, Francisco Javier Moreno
Abstract: This article presents an open discussion of the processes of urban secession and gentrification in contemporary European cities, arguing that intergroup social dynamics in urban spaces are generally more complex than either extreme mutual avoidance or the colonization of neighbourhoods by the wealthiest groups. We analyse the residential strategies of urban upper‐middle class managers in various European metropolitan areas through in‐depth semi‐structured interviews to argue that these groups develop complex strategies of proximity and distance in relation to other social groups. The development of these 'partial exit' strategies takes place through specific combinations of practices that allow groups to select the dimensions they are willing to share with other social groups, and those in which they prefer a more segregated social environment for themselves and their families. The responses of our interviewees were consistently more nuanced and complex than suggested by a simplistic theory about their drive to withdraw from society, forcing us to develop more sophisticated conceptual frameworks to account for the growing prevalence of multi‐layered identities and spheres of reference and solidarity, specific combinations of elective segregation and local involvement, and more active patterns of mobility combined with local embeddedness.